Hybrid algorithm for NARX network parameters' determination using differential evolution and genetic algorithm - Salami, Momoh Jimoh Eyiomika; Tijani, Ismaila; Isqeel , Abdullateef Ayodele; Aibinu, Abiodun Musa (IOP Publishing, 2013)
A hybrid optimization algorithm using Differential Evolution (DE) and Genetic Algorithm (GA) is proposed in this study to address the problem of network parameters determination associated with the Nonlinear Autoregressive with eXogenous inputs Network (NARX-network). The proposed algorithm involves a two level optimization scheme to search for both optimal network architecture and weights. The DE at the upper level is formulated as combinatorial optimization to search for the network architecture while the associated network weights that minimize the prediction error is provided by the GA at the lower level. The performance of the algorithm is evaluated on identification of a laboratory rotary motion system. The system identification results show the effectiveness of the proposed algorithm for nonparametric model development.